Breath acetone concentration decreases with blood glucose concentration in type I diabetes mellitus patients during hypoglycaemic clamps - Turner, Claire; Walton, Christopher; Hoashi, Shu; Evans, Mark (IOP Publishing, 2009)
Conventional wisdom is that breath acetone may be markedly elevated in type 1 diabetes, but that this only occurs during poor blood glucose control and/or intercurrent illness. In contrast, little is known about breath acetone at more representative everyday blood glucose levels in diabetes. We used selected ion flow tube mass spectrometry to monitor the breath of eight patients with type 1 diabetes mellitus during 'insulin clamp' studies in which insulin and glucose were infused into patients to lower blood glucose levels in steps from normal values into the low glucose (hypoglycaemic) range. The concentration of acetone in breath and the blood sugar concentration of the patients were monitored at each blood glucose concentration. The blood glucose level at the start of the study was typically about 6 mM L-1, whereas the breath acetone concentration at this blood glucose level was unexpectedly variable, ranging from 1 part-per- million to 21 ppm, in contrast to what was previously believed, i.e. that type 1 diabetes mellitus is characterized by high acetone levels. In all eight patients, the breath acetone declined linearly with blood glucose concentration.